DISORDERS OF PLASMA AND PLATELET PATHWAYS OF HEMOSTASIS IN PATIENTS WITH ARTERIAL HYPERTENSION COMBINED WITH DISLIPOPROTEINEMIA - M. Y. Zhuk; V. A. Metelskaya; N. V. Perova; N. I. Zhidko; D. M. Aronov; R. G. Oganov (Российский кардиологический журнал)
Parameters of lipid transport system as well as that of haemostasis have been studied in coronary heart disease (CHD) patients (n = 70) having at least one of two major CHD risk factors - arterial hypertension (AH) and dyslipoproteinemia (DLP). Patients with combination of AH and DLP significantly differed from those with isolated DLP by higher levels of total and low density lipoprotein cholesterol, triglycerides and apolipoprotein B. As compared with patients with isolated AH they differed by elevated systolic and diastolic blood pressure. The increased blood thrombogenicity (combination of disturbances in haemostasis resulted in enhanced thrombosis) was high both in hypertensive and dyslipidemic subjects. However, while in group with isolated DLP there was a predominance of decreased anticoagulation and fibrinolysis, in patients with isolated AH the major impact was related to elevated platelet aggregation. Thus, unfavorable shifts in lipoprotein and haemostasis parameters found in patients with AH and DLP could be regarded as markers of their atherothrombogenicity.